Molecular and Host Lifestyle Factors Associated with Persistent Human Papillomavirus Infection and Progression into Cervical Cancer: A Literature Review - Yo, Edward Christopher; Nuryanto, Kartiwa Hadi (http://dharmais.co.id/, 2024)
Background: Human papillomavirus (HPV) infection is the most common sexually transmitted infection (STI) worldwide, especially among low- and middle-income countries. The virus can establish persistent infection in the cervical epithelium, thereby increasing the risk of progression into cervical cancer. Since cervical cancer is one of the leading causes of cancer death among women worldwide, it is important to understand more about persistent HPV infection and potential therapeutic targets to suppress it. This study aims to summarize current insight into various molecular and host lifestyle factors that contribute to persistent HPV infection and ultimately cervical cancer. Methods: This study adopts a literature review design by conducting a journal search through Google Scholar, PubMed, and ScienceDirect. The keywords used included “human papillomavirus”, “persistent infection”, “cervical cancer”, “immune evasion”, and “lifestyle”. Results: Several diverse mechanisms are believed to facilitate persistent HPV infection, which can be classified under molecular and host lifestyle factors. Molecular factors include compartmentalization of HPV replication and gene expression as well as immune evasion, whereas host lifestyle factors include alcohol consumption, smoking, multiple sexual partners, STI coinfection, and certain contraceptive agents. Conclusion: Persistent HPV infection acts as the intermediate phenotype before developing into cervical cancer. Understanding the molecular factors as well as host lifestyle factors underlying it can lead to more specific therapeutic options as well as better prevention and education programs. Future research is needed to better clarify the exact mechanisms underlying persistent infection.